Optimasi Produksi Benih Padi (Oryza sativa L.) Hibrida dengan Aplikasi GA3 - Wahyuni, Mela; Surahman, Memen; Qadir, Abdul; Satoto, Satoto (Jurnal Penelitian Pertanian Tanaman Pangan, 2017)
The low production of hybrid rice seed is influenced by the syncronized of flowering time between CMS and restorer. One of several ways to syncronize both two CMS and restorer was use gibberellins. Gibberellins as growth regulator worked by triggered plant growth and flowering. The objective of this research was to obtain the optimal concentration of GA3 to support the increase hibryd rice seed production. The experiment was arranged in a split plot design based on randomized complete block design. The first factor was three hybrid rice varieties (V) i.e. V1 Hipa-8 (A1 and PK91), V2 Hipa-14 (A7 and PK92) and V3 Jatim-3 (A6 and PK88) belong to the Center for Rice Research (BB Padi) as the main plot and the second factor was four level concentrations of gibberellins (GA3) i.e. G0 (without GA3), G1 (GA3 150 ppm) G2 (GA3 200 ppm) and G3 (GA3 250 ppm) as a subplot. The treatment was performed by spraying GA3 with spray volume of one liter per a plot on the female and male parent. The results of experiment showed that concentrations of GA3 treatment significantly increased plant height, angle of floret opening and decreased number of empty spikelets. The treatment interaction of GA3 concentration and variety significantly effected on percentage of increasing plant height and productivity. The highest productivity was rice hibryd of A7 (Hipa-14) of 1 000 kg/ha with application of 200 ppm GA3.